Point Cloud Domain Adaptation via Masked Local 3D Structure Prediction - Liang, Hanxue; Fan, Hehe; Fan, Zhiwen; Wang, Yi; Chen, Tianlong; Cheng, Yu; Wang, Zhangyang (European Conference on Computer Vision (ECCV 2022), 2022)
The superiority of deep learning-based point cloud representations relies on large-scale labeled datasets, while the annotation of point clouds is notoriously expensive. One of the most effective solutions is to transfer the knowledge from existing labeled source data to unlabeled target data. However, domain bias typically hinders knowledge transfer and leads to accuracy degradation. In this paper, we propose a Masked Local Structure Prediction (MLSP) method to encode target data. Along with the supervised learning on the source domain, our method enables models to embed source and target data in a shared feature space. Specifically, we predict masked local structure via estimating point cardinality, position and normal. Our design philosophies lie in 1) Point cardinality reflects basic structures (e.g., line, edge, and plane) that are invariant to specific domains. 2) Predicting point positions in masked areas generalizes learned representations so that they are robust to incompletion-caused domain bias. 3) Point normal is generated by neighbors and thus robust to noise across domains. We conduct experiments on shape classification and semantic segmentation with different transfer permutations and the results demonstrate the effectiveness of our method.